All the ills that flesh is heir to [Internet viruses]. - Cherry, S.M.
Bugbear, the newest Internet virus, was first spotted in Malaysia on 29 September 2002. Within 24 hours, it was found in over 100 countries; in its first week, it infected over a million computers. Its shaping up to be one of the worst viruses so far. Instead of trashing files, or overloading networks and bringing them to their knees, as did the infamous Nimda and Melissa, Bugbear can quietly log passwords and credit card numbers, and leave them exposed on the Internet. What's more, it can leave the computers and networks it infects open and at the mercy of hackers and future viruses by deleting antivirus software and firewall protections. Yet as bad as Bugbear is, viruses to come will be much worse, say many computer experts. They're reluctant to talk about the problem, in part because they fear giving virus writers helpful hints. Nor do they want to say anything that might be taken as a challenge. Arguably the biggest threat the Internet faces today is the propagation of a big worm.
Keywords: Bugbear; Internet virus; Antivirus software deletion; Credit card numbers logging; Firewall protection deletion; Hackers; Passwords logging; Worm propagation